Evaluation of Digital Capabilities and Digital Marketing Practices of Micro, Small, and Medium Business in Toba Regency - Verawaty Situmorang; Mariana Simanjuntak; Parmonangan Togatorop; Yohanssen Pratama (Institute of Computer Science (IOCS), 2022)
The era of disruption is marked by the presence of various innovations, technologies, platforms, and new business models. This era opens up opportunities for Micro, Small, and Medium Enterprise (MSME) to grow. Initial observations that aimed at Toba MSME actors show that the use of digitalization for marketing is still very low. This prompted to conduct the research with purpose to find out the possibility of how the implementation of MBKM can help accelerate the digitization of Toba MSMEs. The data collection method was carried out by surveying students, lecturers and staff as interested parties in MBKM, and continued with Focus Group Discussions with Toba MSME actors. Through this study, an evaluation of the digital capabilities and implementation of e-marketing of Toba MSME actors was carried out in order to produce further recommendations and obtaining the results in the form of an overview of Toba MSME digital capabilities based on aspects of ‘digital innovation, digital technology, digital orientation, digital capability, and marketing capability’. From this research we found that the most common obstacles faced by Toba MSME actors are the limited digital literacy of MSME actors, limited capital, lack of understanding of marketing concepts and practices, and limited number of human resources. These limitations are very likely to be resolved with the MBKM program so that the acceleration of the Toba MSME digital transformation can be carried out.